2022
DOI: 10.3389/fmicb.2022.996930
|View full text |Cite
|
Sign up to set email alerts
|

Screening of cellulose-degrading yeast and evaluation of its potential for degradation of coconut oil cake

Abstract: Coconut oil cake (COC), a byproduct of oil extraction, contains high levels of cellulose. The aim of this study was to isolate a cellulose-degrading yeast from rotten dahlia that can effectively use COC as the only carbon source for cellulase secretion. Based on screening, Meyerozyma guillermondii CBS 2030 (M. guillermondii) was identified as a potential candidate, with the highest cellulolytic activity among the yeast strains isolated, with the carboxymethyl cellulase (CMCase) activity reaching 102.96 U/mL on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“… Yan et al (2021) found that the CrI value of corn stover increased after treatment, as the degradation of amorphous biomass, including hemicellulose, which exposed more binding sites. Our research results are also consistent with those of Fu et al (2022) , who found that the crystallinity index of coconut oil residue increased after treatment with M. guillermondii .…”
Section: Discussionsupporting
confidence: 93%
“… Yan et al (2021) found that the CrI value of corn stover increased after treatment, as the degradation of amorphous biomass, including hemicellulose, which exposed more binding sites. Our research results are also consistent with those of Fu et al (2022) , who found that the crystallinity index of coconut oil residue increased after treatment with M. guillermondii .…”
Section: Discussionsupporting
confidence: 93%
“…Screening for the decomposition of cellulose has been widely performed using Congo red. Cellulolytic microorganisms possess the ability to degrade non-crystalline sections of cellulose, leading to a loss of Congo red binding and a visible halo around the colony (Fu et al 2022). The larger the size of the transparent zone around the colony diameter, the higher the activity of the cellulose produced (Li et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, the color of the samples was determined using an SPH 860 colorimeter (Colorlite, Katlenburg-Lindau, Germany). COC color was evaluated from three aspects using the CIE Lab color system, where an appropriate amount of dry powder was placed on the sample plate to directly measure the color L*, a* and b* coordinates [ 19 ]. Each value was measured nine times, and the average value was taken.…”
Section: Methodsmentioning
confidence: 99%
“…As an alternative to fungi, bacteria are now being explored for use in the enzymatic hydrolysis of lignocellulose due to their high rate of enzyme production, expression of multi-enzyme complexes, tolerance to extreme environments, and the ability to be genetically engineered [ 5 , 18 ]. Previous studies have reported the isolation of cellulose-degrading bacteria from nature to modify the recalcitrant structure of cellulose to add value [ 19 ]. Therefore, the screening and identification of high-efficiency cellulolytic bacteria can provide insight into cellulose degradation mechanisms and inspire methods to improve the utilization rate of cellulose resources.…”
Section: Introductionmentioning
confidence: 99%